2001
DOI: 10.1016/s0042-6989(01)00166-3
|View full text |Cite
|
Sign up to set email alerts
|

Fixation location effects on fixation durations during reading: an inverted optimal viewing position effect

Abstract: Previous research has found that words are identified most quickly when the eyes are near their center (the Optimal Viewing Position effect). A study was conducted to determine whether this same phenomenon is observed during reading, as revealed by a relationship between fixation position in a word and the duration of the fixation. An analysis of three large existing corpora of eye movement data, two from adults and one from children, showed a surprising inverted Optimal Viewing Position curve: mean fixation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

41
241
8
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(294 citation statements)
references
References 28 publications
41
241
8
2
Order By: Relevance
“…The probability of the eyes initially fixating a given letter position is estimated by the relative frequency in the corpus. These data exhibit the typical properties of the landing position distributions that have been reported by other researchers (e.g., McConkie et al, 1988;Rayner, 1979;Vitu et al, 2001). First, the curves for shorter words are flatter than those for longer words (the mode of the curve is more easily distinguished for longer words); second, the majority of the probability mass is distributed over the first half of the word.…”
supporting
confidence: 84%
“…The probability of the eyes initially fixating a given letter position is estimated by the relative frequency in the corpus. These data exhibit the typical properties of the landing position distributions that have been reported by other researchers (e.g., McConkie et al, 1988;Rayner, 1979;Vitu et al, 2001). First, the curves for shorter words are flatter than those for longer words (the mode of the curve is more easily distinguished for longer words); second, the majority of the probability mass is distributed over the first half of the word.…”
supporting
confidence: 84%
“…(2) These cases immediately trigger a new saccade program. Interestingly, the IOVP effect appears to be largely independent of word frequency (i.e., the curve is simply elevated for low-frequency words; Nuthmann et al, 2005;Rayner, Sereno, & Raney, 1996;Vitu et al, 2001) and, therefore, represents a comparatively confined contribution of oculomotor errors to fixation durations. …”
mentioning
confidence: 99%
“…Whatever the disadvantages of our methodology may be, the pattern of results that we have obtained and reported either in the body of the paper or in Appendix 1, dovetails perfectly with many of the results obtained in the literature for sentential reading, such as visuo-oculomotor effects (cf., e.g., O'Regan et al, 1994;Rayner, 1998;Vitu, McConkie, Kerr & O'Regan, 2001), effects of compound length and frequency, as well as of constituent frequencies (cf., e.g., Andrews et al, 2004;Duñabeitia, Perea & Carreiras, 2007;Hyönä & Pollatsek, 1998;Hyönä et al, 2004;Juhasz et al, 2003;Taft & Forster, 1976), and effects of orthographic n-grams (reported in Appendix 1, cf., e.g., Lima & Inhoff, 1985). Furthermore, in a recent sentential reading study (Kuperman, Bertram & Baayen, 2008), in which Finnish compounds were embedded in context, a highly similar pattern of results was observed, including early effects of compound frequency, left constituent frequency and family size, later and weaker effects of right constituent frequency and family size, interactions between morphological predictors, as well as longitudinal experimental effects.…”
mentioning
confidence: 99%